Proton pump inhibitor use and risk of depression among Sudanese adults: a cross-sectional community-based study - Alwabili, Afnan A.; Omar, Saeed M.; Alotaibi, Eman A.; Adam, Ishag (Frontiers in Psychiatry, 2026)
BackgroundDepression is a major global public health issue. There is little available data regarding the association between the use of proton pump inhibitors (PPIs) and depression. The current study aimed to investigate the association between PPIs and depression among adults in Central Sudan.MethodsA community-based cross-sectional study was conducted to examine adults in Central Sudan. Sociodemographic data and medical history were collected. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Multivariate binary regression analyses, modified Poisson regression analyses, and propensity score matching (PSM) were performed.ResultsWe enrolled 914 adults (317 [34.7%] men and 597 [65.3%] women). Participants’ median (interquartile range) age was 38.0 (27.0–52.0) years. Of the participants, 255 (27.9%) had used PPIs. In Poisson regression, after adjusting for confounders (age, sex, education, occupation, marital status, hypertension, diabetes mellitus, body mass index, smoking, alcohol), use of PPIs [adjusted relative risk = 1.30, 95% confidence interval (CI) = 1.21–1.40] was associated with a higher depression score. Of 914 adults, 155 (17.0%) had depression (PHQ-9 score of ≥ 8). Before matching (PSM), in multivariate binary regression (after removing confounders), PPIs were associated with depression [adjusted odds ratio (AOR)= 1.64; 95% CI = 1.14–2.37]. After matching, PPIs were associated with depression (AOR = 1.66; 95% CI = 1.13–2.41).ConclusionThis study revealed a positive association between PPI use and depression. Longitudinal studies will be necessary to examine this relationship in more depth.